2016
DOI: 10.1111/acv.12250
|View full text |Cite
|
Sign up to set email alerts
|

High genetic variability of vagrant polar bears illustrates importance of population connectivity in fragmented sea ice habitats

Abstract: Projections by the Intergovernmental Panel on Climate Change (IPCC) and sea ice forecasts suggest that Arctic sea ice will decline markedly in coming decades. Expected effects on the entire ecosystem include a contraction of suitable polar bear habitat into one or few refugia. Such large-scale habitat decline and fragmentation could lead to reduced genetic diversity. Here we compare genetic variability of four vagrant polar bears that reached Iceland with that in recognized subpopulations from across the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…For some species, habitat suitability models from parts of their range are thus not reliably transferrable to other regions, with important consequences for management (Bain et al, 2015 ; Denryter et al, 2017 ). Ecological knowledge of the species under study can provide perspectives on whether observed animal movements are common or atypical; for example, regarding sex‐biased dispersal (Støen et al, 2006 ), and the occurrence of seasonal movements in species that are usually nonmigratory (Musiani et al, 2007 ) or exhibit vagrant behaviour (Kutschera et al, 2016 ). Ecological data can also be combined with information on the spatial distribution of genetic variation as indicators of local adaptations (Fitzpatrick et al, 2015 ) or responses to ongoing environmental change (Koen et al, 2014 ; Kutschera et al, 2016 ).…”
Section: A Framework and Recommendations For Incorporating Genetic St...mentioning
confidence: 99%
“…For some species, habitat suitability models from parts of their range are thus not reliably transferrable to other regions, with important consequences for management (Bain et al, 2015 ; Denryter et al, 2017 ). Ecological knowledge of the species under study can provide perspectives on whether observed animal movements are common or atypical; for example, regarding sex‐biased dispersal (Støen et al, 2006 ), and the occurrence of seasonal movements in species that are usually nonmigratory (Musiani et al, 2007 ) or exhibit vagrant behaviour (Kutschera et al, 2016 ). Ecological data can also be combined with information on the spatial distribution of genetic variation as indicators of local adaptations (Fitzpatrick et al, 2015 ) or responses to ongoing environmental change (Koen et al, 2014 ; Kutschera et al, 2016 ).…”
Section: A Framework and Recommendations For Incorporating Genetic St...mentioning
confidence: 99%
“…Future sea-ice loss is expected to fragment polar bear subpopulations, increase isolation, alter gene flow, and disrupt population boundaries (Derocher, Lunn, & Stirling, 2004;Kutschera et al, 2016;Sahanatian & Derocher, 2012). Genetic variation in polar bears is relatively low, and genetics is a relatively insensitive means of identifying, defining, or detecting change in subpopulation structure, especially when compared to individual-based telemetry and tag recoveries.…”
Section: Genetic Connectivity Between Subpopulationsmentioning
confidence: 99%
“…Likely having persisted for several hundred thousand years, polar bears as a species have experienced several glacial cycles. However, the polar bear genome carries testimony of past population bottlenecks that were presumably linked to environmental changes such as interglacial warm phases -indicative of vulnerability to climatic changes (Durner et al 2009;Peacock et al 2015;Kutschera et al 2016). In addition, although polar bears have persisted through previous warm phases, multiple current human-mediated stressors (e.g., habitat conversion, persecution, and accumulation of toxic substances in the food chain) are magnifying the impacts of current climate change.…”
Section: Discussionmentioning
confidence: 99%